2015
DOI: 10.1107/s2056989015016102
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of 5-chloro-1,3-bis[2-(2-oxo-1,3-oxazolidin-3-yl)ethyl]-1H-benzimidazol-2(3H)-one

Abstract: In the title compound, C17H19ClN4O5, the benzimidazole fused-ring system is essentially planar, the maximum deviation from the mean plane being 0.06 (1) Å. Both oxazolidine rings are nearly planar, the maximum deviations from the mean planes are 0.071 (13) and 0.070 (10) Å. The dihedral angle between the mean planes of the oxazolidine rings is 69.9 (7)°. The benzimidazole mean plane makes the dihedral angles of 43.9 (6) and 45.6 (6)° with the two oxazolidine rings. In the crystal, the mol­ecules are linked tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…An N-substituted benzoimidazol-2-one analogue (Saber et al, 2018a,b;Saber et al, 2020) and other similar compounds have also been reported (Belaziz et al, 2012(Belaziz et al, , 2013Bouayad et al, 2015). In derivatives of benzimidazolin-2-one in which both nitrogen atoms form exocyclic C-N bonds, the bicyclic ring system is either planar, has a slight twist end-to-end, or, in the cases where the exocyclic substituents form a ring, has a very shallow bowl shape.…”
Section: Database Surveymentioning
confidence: 92%
“…An N-substituted benzoimidazol-2-one analogue (Saber et al, 2018a,b;Saber et al, 2020) and other similar compounds have also been reported (Belaziz et al, 2012(Belaziz et al, , 2013Bouayad et al, 2015). In derivatives of benzimidazolin-2-one in which both nitrogen atoms form exocyclic C-N bonds, the bicyclic ring system is either planar, has a slight twist end-to-end, or, in the cases where the exocyclic substituents form a ring, has a very shallow bowl shape.…”
Section: Database Surveymentioning
confidence: 92%
“…The syntheses of several N-substituted benzimidazol-2-one analogues have been reported (Saber et al, 2018a,b;2020;Belaziz et al, 2012;Bouayad et al, 2015;Belaziz et al, 2013). In a search of the Cambridge Crystallographic Database (CSD; Version 5.40, update of September 2019; Groom et al, 2016) using benzimidazol-2-one with an exocyclic carbon atom bound to each nitrogen generated 94 hits.…”
Section: Database Surveymentioning
confidence: 99%